Perencanaan dan Pengelolaan Keuangan Keluarga pada Ibu Rumah Tangga Desa Kaliburu - Abd. Hafizh Amang Rustamin; Niluh Putu Evvy Rossanty; Harnida Wahyuni Adda (Pusat Riset dan Inovasi Nasional, 2023)
Family financial planning and management counseling activities for housewives were carried out in Kaliburu Village, Sindue Tombusabora District, Donggala Regency, Central Sulawesi. Housewives play an important role as regulators of family finances. The background to the implementation of this activity is that there are still many people who spend money beyond what is needed and beyond their own income, so that they are trapped in debt and unable to pay bills on the grounds that they are running out of funds. This counseling activity was carried out with the aim of providing an understanding of housewives in Kaliburu Village so that they know the importance of planning and how to carry out good family financial management. This activity was attended by 10 participants on Thursday, December 22, 2022. The methods used were counseling, discussion, and question and answer. This activity was carried out well, it can be seen from the results after counseling 100% of participants understood the importance of family planning, before counseling only 30% of participants. Participants who knew how to plan and manage family finances reached 80% from only 20% previously. Participants who had carried out family financial planning well reached 50%, previously only 10%.